La notte di Milano: problemi e opportunità in una fase di rigenerazione urbana - Simone Gamba (Bollettino della Società Geografica Italiana)
Milan is experiencing a period of intense urban renewal affecting nightlife as never before. In this transformation process changes occur both in central and peripheral areas, due to a notable proliferation of events, diffusion of social media and new technologies for mobility in a general framework of festivalization and dayfication of the night. This paper aims to investigate the ongoing co-evolution of the Milanese neighborhoods, their nightlife and some related issues such as: noise thresholds, public safety, modification of rhythms and spaces that also produce a conflict between daily and night inhabitants. Finally, the analysis includes a case study on an innovative accommodation solution (Ostello Bello) which, thanks to its 24/7 services and frequent events, allows meetings between tourists and city dwellers.